2009
DOI: 10.1203/pdr.0b013e31819ed68d
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Reduces the Cytokine-Mediated Inflammation but Does Not Suppress Cellular Infiltration of the Vessel Wall in Refractory Kawasaki Disease

Abstract: ABSTRACT:The aim of our study was to evaluate the efficacy of infliximab for the treatment of patients with refractory Kawasaki disease (KD) and investigate the dynamic changes of cytokines during infliximab treatment. We have performed a study of cytokine and proinflammatory molecule levels in 43 KD patients including 18 responders to IVIG, 14 nonresponders, and 11 patients treated with infliximab. We determined serum levels of soluble TNF receptor I (sTNFR I) and IL-6, as well as VEGF, damage associated mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…The increased transcript abundance of several genes in the IL-1 pathway has been confirmed among IVIG-resistant KD subjects (13). Meanwhile, another study reported that the serum levels of soluble TNF receptor 1 and IL-6 are dramatically decreased after IFX therapy in refractory KD subjects (9). In this study, IFX therapy greatly suppressed the expression levels of transcripts, which are involved in the main pathways of cytokine signaling related to KD vasculitis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The increased transcript abundance of several genes in the IL-1 pathway has been confirmed among IVIG-resistant KD subjects (13). Meanwhile, another study reported that the serum levels of soluble TNF receptor 1 and IL-6 are dramatically decreased after IFX therapy in refractory KD subjects (9). In this study, IFX therapy greatly suppressed the expression levels of transcripts, which are involved in the main pathways of cytokine signaling related to KD vasculitis.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, the use of IFX has been attempted as a novel therapy for refractory KD (6)(7)(8)(9). In a randomized study of additional IVIG vs. IFX infusion in KD patients with fever following initial treatment with IVIG, IFX infusion was found to be safe and well tolerated in KD patients, with no serious adverse reactions attributed to either therapy.…”
mentioning
confidence: 99%
“…Proinflammatory cytokine levels fell after infliximab treatment, but markers of vasculitis, including vascular endothelial growth factor and the S100 proteins, remained elevated. 196 This suggested the possibility that infliximab was effective in reducing systemic levels of inflammation but not in suppressing the vasculitis.…”
Section: Infliximabmentioning
confidence: 99%
“…The immune-suppressing effects of IVIG in patients with Kawasaki disease and, more importantly, its ability to prevent the development of coronary artery aneurysms might relate to the neutralizing antibody activity in IVIG against these bacterial enterotoxins 26 and proinflammatory cytokines. 29 It was also shown in patients with Kawasaki disease that IVIG therapy could modify the production of cytokines by mononuclear cells. IVIG inhibits the production of IL-1, TNF-a, TNF-b, and IFN-g by PBMCs stimulated with bacterial superantigens or LPS while increasing the production of IL-1 receptor antagonist, an anti-inflammatory cytokine that counteracts the effects of IL-1.…”
Section: Suppression Of Cytokine Productionmentioning
confidence: 99%